Procuring a sustainable future: an action learning approach to the development and modelling of ethical and sustainable procurement practices. (1st September 2016) - Boak, George; Watt, Peter; Gold, Jeff; Devins, David; Garvey, Robert
ABSTRACT: This paper contributes to an understanding of the processes by which organisational actors learn how to affect positive and sustainable social change in their local region through action learning, action research and appreciative inquiry. The paper is based on a critically reflective account of key findings from an ongoing action research project, funded by the Joseph Rowntree Foundation. The project is an attempt to alleviate poverty in the Leeds City Region through the identification and spread of 'good practice' in large local organisations. The paper is based on insights into the tensions involved in accomplishing such modes of action research and action learning in this particular context, and how these findings can relate to similar research in other domains of inquiry, action and cross-organisational learning. Through this, the paper discusses the inherent challenges faced when attempting to use action research and action learning approaches to help large organisations to learn and develop as ethical and sustainable agents.